STRATEGY FOR SUCCESSFUL IMPLEMENTATION OF THE ZAKAT VILLAGE INDEX THROUGH HUMAN RESOURCE DESIGN IN THE ZAKAT VILLAGE PROGRAM, SIDOARJO REGENCY - Bayu Wardhana; Sigit Hermawan; Hadiah Fitriyah (Universitas Islam Negeri Mataram, 2023)
The Zakat Village Index can be interpreted as a measuring tool that zakat managers can use to know the condition of a village and whether the village is eligible for assistance. This research was conducted to analyze the success of the zakat village implementation strategy through the design of human resources in the zakat village program in Sidoarjo Regency. The problem is that in implementing the Zakat Village Index, there are obstacles, namely limited human resources. The research method used is interpretive qualitative by collecting data through in-depth interviews, FGDs and documentation. The data used is primary data with the research object, namely the zakat village program in Sidoarjo Regency. The results of the study show several obstacles related to the implementation of the Zakat Village Index in the zakat village, including the first is, limited human resources, the second is management competency and the third is workload. To overcome these problems, a solution is needed, namely collaboration between agencies. Competency development also needs to be carried out, including increasing employee competence on the work village index, evaluating workload and the role of leaders in implementing the Zakat Village Index in the zakat village program. The implications of this research are expected to create a human resource design strategy for the zakat village program in Sidoarjo Regency with the implementation of the Zakat Village Index.